Psychosocial risk management in the New Zealand public sector : a sociotechnical systems analysis of executive leaders’ perspectives of barriers and enablers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Wellington, New Zealand - Thompson, Amelia May Margaret (Massey University, 2025)
Work-related psychosocial harm remains a persistent and complex challenge for many organisations. Despite legal, ethical, and financial imperatives to manage psychosocial risks, many organisations continue to struggle in practice. The reasons for this are seldom straightforward and rarely attributable to a single cause; rather, they arise from the interplay of numerous factors that collectively constrain effective psychosocial risk management. Existing frameworks tend to focus narrowly on the individual or organisational level, overlooking the broader systemic dynamics that shape how psychosocial risks are generated, transmitted, and controlled. In contrast, other safety domains recognise that risks must be understood within a multi-layered sociotechnical system comprising macro-, meso-, and micro- levels, each with its own actors and interdependencies. To address this gap, this study applies a sociotechnical systems lens to examine the barriers and enablers influencing psychosocial risk management within the New Zealand public sector, specifically the perspectives of those with the greatest influence on organisational performance – its executive leaders. Adopting a critical-realist epistemology and an abductive, qualitative design, twelve semi structured interviews were conducted with public sector executive leaders. Reflexive thematic and content analyses were used to identify patterns of meaning and systemic dynamics shaping psychosocial risk management practices. This process generated overarching thematic insights which were interpreted in light of existing literature, sector specific knowledge, and systems-based safety theory. Findings reveal that numerous barriers and enablers operate simultaneously across multiple system levels, ultimately influencing psychosocial risk management. This included political expectations, fiscal restraint, media scrutiny, fragmented accountability, inadequate organisational systems and capabilities. Critically, the research identifies impairments in feedback, where information about risk and harm becomes diluted or reframed as it moves through the system, undermining learning and assurance. These findings illuminate why psychosocial risk remains challenging to manage in complex organisational systems and demonstrates the value of applying sociotechnical systems theory to psychosocial risk management, as has been done in other safety domains.
Figure 6 is © Emerald Group Publishing Limited so was removed for copyright reasons. Figure 12 is reproduced under a Creative Commons Attribution 4.0 International (CC BY 4.0) license.
Keywords: 520104 Industrial and organisational psychology (incl. human factors); 350707 Leadership